All Days 2014
DOI: 10.2118/172278-ms
|View full text |Cite
|
Sign up to set email alerts
|

Do Not Let Temperature Transients Hinder Your Build-up Pressure Interpretation – Proper Gauge Placement in Highly Productive Reservoirs in Well Testing Operations

Abstract: Quality of well testing in highly productive reservoirs directly depends on the pressure-gauge placement in the wellbore. This paper documents the impact of the placement of downhole gauges on pressure transient analysis (PTA) for high-productivity reservoirs. The article illustrates cases where this latetransient behavior is strongly influenced by temperature effects, which can lead to significant errors if not considered during the interpretation process.Although the correction of measured pressure to datum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In particular, a large pressure drop may occur in the tubing while the string moves between various sequences during the test. Liquid dropout and fluid segregation effects in the wellbore during pressure build-up could also mislead the interpretation, in particular in prolific formations tested under moderate drawdown (Sidorova et al, 2014). These effects can mask or at least distort the actual reservoir pressure response and can quite often lead to a misinterpretation of the well test data and a misunderstanding of the reservoir structure and associated parameters.…”
Section: Representative Evaluation Of Completion Performancesmentioning
confidence: 99%
“…In particular, a large pressure drop may occur in the tubing while the string moves between various sequences during the test. Liquid dropout and fluid segregation effects in the wellbore during pressure build-up could also mislead the interpretation, in particular in prolific formations tested under moderate drawdown (Sidorova et al, 2014). These effects can mask or at least distort the actual reservoir pressure response and can quite often lead to a misinterpretation of the well test data and a misunderstanding of the reservoir structure and associated parameters.…”
Section: Representative Evaluation Of Completion Performancesmentioning
confidence: 99%
“…The authors demonstrated that temperature data can provide valuable information regarding the existence of multiple fractures and any eventual crossflow between them. Sidorova et al (2014) investigated the impact of downhole gauge location on conventional pressure transient analysis in the case of high-productivity reservoirs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some test strings are designed with gauge adapters placed below expansion joints, hence their locations are fixed. Conversely, some test strings may account for packers that compensate for string movement (Sidorova et al, 2014). Therefore, both constant and variable pipe-length solutions will be assessed.…”
Section: Synthetic Case Studymentioning
confidence: 99%
See 1 more Smart Citation